PANDANGAN FILSAFAT TERHADAP ILMU KEOLAHRAGAAN PADA PENDIDIKAN GENERASI Z - Maulana Putra, Ikhsan (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Philosophy of Sport is a branch of philosophy that analyzes the concept of sport as part of human activity. In its development, the philosophy of sport discusses metaphysics and ethical and moral philosophy. This study aims to understand the basic concept of the philosophy of sports science in Generation Z Education. It uses a literature study method with secondary data collection from books and scientific articles. The results of this literature research show the importance of conducting research in the form of searching for information about sports today from the perspective of sports philosophy. Philosophy and education are closely related to making each individual aware of constructive critical thinking. In line with that, learning activities in sports for Generation Z must prioritize cooperation and minimize unsportsmanlike competition for mutual progress. Generation Z must have the motivation to support the quality of sports education. So, every Generation Z needs to make sports philosophy a foundation in learning practices.